Analysis of the Impact of Online Games on Time Management at Junior High School Negeri 2 Tanjung - Muhamad Syarpani; Eka Purnama Indah; Edwin Wahyu Dirgantoro (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the impact of playing online games on student time management at Junior High School Negeri 2 Tanjung. The research method used is quantitative descriptive. Meanwhile, the sampling technique applied in this study was 50% random sampling, which was 60 students. The results of the research in this journal are analysis of the impact of online games and time management of the two indicators after going through the recategorization test included in the category of enough with it can be concluded that the impact of online games shows a percentage of 56%, which means that more than half of the respondents are aware of the negative effects of online gaming activities. Meanwhile, in time management, a percentage of 52% was obtained, indicating that the majority of students experienced negative changes or challenges in managing time due to playing online games. This indicates that online games not only affect students’ behavior, but also impact their ability to manage time effectively.